2015
DOI: 10.4278/ajhp.130625-arb-323
|View full text |Cite
|
Sign up to set email alerts
|

Our Health Is in Our Hands: A Social Marketing Campaign to Combat Obesity and Diabetes

Abstract: Purpose. Design, implement, and evaluate a 6-week social marketing campaign (SMC) to raise awareness of obesity and increase involvement in type 2 diabetes prevention, nutrition, and fitness programs offered by the Brooklyn Partnership to Drive Down Diabetes (BP3D) in two low-income, urban communities.Design. This was a nonexperimental, formative research, mixed-methods study.Setting. The study took place in Central Brooklyn and East New York, two of the most impoverished, high-need communities in New York Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…Enthusiasm for electronic media has led to hopes that population interventions might harness the power of electronic media to build virtual communities, promote information sharing, and support behavioral change. In turn, the use of such media could result in cost savings in comparison with traditional human-to-human interactions, [10][11][12]25,26 Families Defeating Diabetes can provide some insights into these areas. First, electronic media transforms itself very rapidly: when FDD was designed, Websites and blogs were mainstream, with most homes having a desktop computer and monitor.…”
Section: Engagement Rates and Correlations With Program Componentsmentioning
confidence: 99%
“…Enthusiasm for electronic media has led to hopes that population interventions might harness the power of electronic media to build virtual communities, promote information sharing, and support behavioral change. In turn, the use of such media could result in cost savings in comparison with traditional human-to-human interactions, [10][11][12]25,26 Families Defeating Diabetes can provide some insights into these areas. First, electronic media transforms itself very rapidly: when FDD was designed, Websites and blogs were mainstream, with most homes having a desktop computer and monitor.…”
Section: Engagement Rates and Correlations With Program Componentsmentioning
confidence: 99%
“…Some small-scale social marketing campaigns to promote healthy eating that incorporate social media platforms have found that people exposed to such campaigns are willing to engage on sites like Facebook and Twitter (George, Roberts, Beasley, Fox, & Rashied-Henry, 2015;Tobey & Manore, 2014). A small study of a Facebook and text message based weight-loss intervention aimed at US college students showed preliminary efficacy and acceptability among users (Napolitano, Hayes, Bennett, Ives, & Foster, 2013).…”
Section: Healthy Eatingmentioning
confidence: 99%
“…George et al (2016) 23 conducted a non-experimental study to design, implement and evaluate a social marketing campaign to increase obesity awareness and involvement in prevention, nutrition and fitness programs in T2DM. To this end, ads in English and Spanish encouraging healthier eating habits and advocating better food choices were shown in a virtual Facebook community.…”
Section: Discussionmentioning
confidence: 99%